Self-supportive virtual communities. (4th December 2009) - Varlamis, Iraklis; Apostolakis, Ioannis
Web-based learning communities allow individuals to improve their skills and knowledge, while offering global distribution of participants and asynchronous participation. Although flexible and distributed, the learning process in such communities is still unidirectional from professors to students. In virtual communities that relate to healthcare, learning and personal improvement is a collaborative process and actions are patient-centric. This work introduces the notion of 'self-supportive virtual communities' – which combine the merits of 'communities of practice' and 'learning communities' and capitalise on the virtual community infrastructures in order to support collaboration of all healthcare participants (i.e., care providers, caregivers and care consumers). This paper discusses the dimensions of the self-supportive community, illustrates the main issues for the transition to the new type of community and summarises the development process of the community. It also gives an example of a self-supportive community for the deaf and the hearing.